Private Rooms in Low Acuity Settings: A Systematic Review of the Literature. (January 2018) - Voigt, Jeffrey; Mosier, Michael; Darouiche, Rabih
Objectives: Determine if the peer-reviewed evidence supports single-patient ward bedrooms in low-acuity care settings within a hospital. Background: New evidence exists since the 2006 Facility Guideline Institute guideline recommended single-bedded rooms (SBRs) in low-acuity care settings. Additionally, prior studies evaluated high-acuity care settings (e.g., critical care) in their recommendations on SBRs. There is a need to reevaluate the evidence. Methods: A systematic review of the literature was completed including electronic and hand searches of references. A data extraction form was utilized. Two reviewers evaluated the studies independently. Studies that were included examined the effect of single-patient rooms on medical surgical ward beds only. Each study was graded using accepted clinical evidence grading instruments. Results: Over 1, 400 records were identified. After excluding studies, a total of 49 records were graded. The highest quality evidence identified (Center for Evidence-Based Medicine [CEBM]: 2a, 2b, and Grading of Recommendations, Assessment, Development, and Evaluation [GRADE] C) did not support the use of single-patient rooms for reducing infections, for minimizing patient falls, for reducing medication errors, or for patient satisfaction. Operational efficiencies were improved with SBRs but only addressed the maternity ward. The lowest quality evidence (CEBM: 4/5 and GRADE D) supported the use of single-patient rooms. Conclusions: Based on CEBM and GRADE assessments, there is a lack of high-quality data supporting the use of low-acuity SBRs throughout the entire hospital. Furthermore, it is recommended that more research be conducted on the effect of SBRs, so higher quality evidence is developed.